Different options for prenatal testing for Huntington's disease using DNA probes. Issue 6 (June 1989) - Fahy, M; Robbins, C; Bloch, M; Turnell, R W; Hayden, M R
Abstract : The discovery of DNA markers closely linked to the gene for Huntington's disease (HD) has allowed development of predictive and prenatal testing programmes for HD. This report describes four different approaches to prenatal testing for HD which have arisen during a pilot predictive and prenatal testing program in British Columbia, Canada. In the first approach (exclusion testing), the at risk parent cannot or prefers not to learn of his/her HD status. Two other approaches involve definitive testing of a fetus when a parent is determined to be at increased risk to have inherited the HD gene or is affected with Huntington's disease. The fourth approach is a stepwise combination of the above two methods which we refer to as 'exclusion-definitive' testing. These different approaches introduce a variety of challenging counselling and ethical issues. The role of each approach to prenatal testing in the management of Huntington's disease awaits the results of this and other predictive and prenatal testing programmes.